The Distribution of Dengue Fever Case Based on Environmental Factors using Spatial Analysis - Meirisa Ayu Hartini; Eram Tunggul Pawenang (Universitas Diponegoro, 2023)
Dengue hemorrhagic fever (DHF) cases in the working area of Margorejo Health Center increased significantly from seven (2021) to 66 (September 2022). One of the efforts to anticipate the disease is acknowledging the distribution pattern of DHF using GIS. This study proposes to reveal the spatial pattern of case distribution, mapping of the vulnerable area, and overlay of LFP (larvae-free rate) related to DHF in the determined working area of Margorejo Health Center. This study was descriptive. The population was patients of DHF. The selected samples were 66. Data were analyzed utilizing univariate and spatial analyses, based on the Average Nearest Neighbor statistical analyses, p-value = 0.001, Z-score = -7.078, and NNI = 0.54<1. These results indicate a clustered spatial pattern, primarily in densely populated areas. The distribution is seen in the buffer area of 250 meters, 750 meters, and 800 meters. The dengue case intensity, population density, and buffer area determine vulnerable areas. Based on the elaborated maps, further, follow-ups related to countermeasures and prevention of DHF are expected to be carried out in the determined area.